Information Invasion of China in Africa - M. V. Khizhnyak (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Over the past decade, China’s information and ideological expansion to Africa has reached an unprecedented scale, accompanying the economic and commercial invasion of the economic giant with the desire to create a new favorable image of the PRC on the continent with the tools of «soft power». Such foreign policy strategy is conditioned by the aspiration to realize the «Chinese dream» — a large-scale plan of the countrydevelopment, implemented throughthe concept «One Belt, One Road». «Road and Belt» cover the entire «World Island» — from Asia to Europe, passing through the countries of the North-East of Africa. This project plays a key role in China’s information invasionin the current millennium.